Owe-017 surveillance for hepatocellular carcinoma: does it improve outcome?. (8th June 2018) - Haq, Mohammad Inamul; Goh, Tee Lin; Ahmed, Asma; Forrest, Ewan; Gillespie, Ruth; Barclay, Stephen; Priest, Matthew; Evans, Jeff; Graham, Janet; Ballantyne, Stuart; Stanley, Adrian
Abstract : Introduction: Surveillance for hepatocellular carcinoma (HCC) is recommended by national and international guidelines. However, there are limited data on the impact of surveillance on clinical outcome. Our aim was to compare the stage of disease at diagnosis, treatment employed and survival, among those patients complying with, not complying with, or never entered into, a surveillance programme over a 7 year period at our regional centre. Methods: We analysed data from our prospectively collected regional HCC MDT database on patients diagnosed with HCC from January 2009 to December 2015. Demographics, Child Pugh score and Barcelona-Clinic Liver Cancer (BCLC) stage at diagnosis were collated, as were the treatment strategy employed and survival. We compared the stage of disease, treatment undertaken and survival across 3 pre-identified groups: 1. Compliant with surveillance (enrolled in surveillance and last ultrasound (US)<9 months of diagnosis of HCC); 2. Poorly-compliant with surveillance (enrolled in surveillance but last US>9 months); 3. Never enrolled into a surveillance programme. Kaplan-Meier, log rank analysis and chi-squared tests were used as appropriate. Results: 641 patients were diagnosed with HCC over this period. Follow up data was available for 638 (99.5%) patients with mean follow-up 15 months. Mean age at diagnosis was 69 years and 82.3% were male. HCC diagnoses increased from 62 in 2009, to 143 in 2015. 52.8% of patients had alcoholic liver diseases, 16.8% NAFLD and 15.4% hepatitis C. 160 (25.1%) patients were from Group 1, 54 (8.5%) from group 2 and 424 (66.5%) from group 3. There was an increase in the proportion of patients with HCC who were diagnosed in a surveillance programme during the study period (p<0.01). BCLC classification 0/A (very early stage) was seen at diagnosis in 38.8% patients in group 1, 16.7% in group 2, and 9.7% in group 3 (p<0.001). Treatment with curative-intent was given to 32.5% patients in group 1, 14.8% in group 2% and 7.8% in group 3 (p<0.001). Mean survival of patients from groups 1, 2 and 3 was 32 months, 14 months and 15 months respectively (p<0.001). Conclusions: The annual number of patients diagnosed with HCC at our regional Centre increased by over 100% during the 7 year study period. A minority of patients diagnosed with HCC were enrolled in a surveillance programme, although the proportion increased over time. HCC Patients enrolled in a surveillance programme had lower BCLC stage at diagnosis, were more likely to receive curative treatment and had improved survival.